A novel mutation in intron 11 donor splice site, responsible of a rare genotype in thyroglobulin gene by altering the pre-mRNA splincing process. Cell expression and bioinformatic analysis. (15th February 2021) - Pio, Mauricio Gomes; Molina, Maricel F.; Siffo, Sofia; Chiesa, Ana; Rivolta, Carina M.; Targovnik, Héctor M.
Abstract: Thyroglobulin (TG) is a homodimeric glycoprotein synthesized by the thyroid gland. To date, two hundred twenty-seven variations of the TG gene have been identified in humans. Thyroid dyshormonogenesis due to TG gene mutations have an estimated incidence of approximately 1 in 100, 000 newborns. The clinical spectrum ranges from euthyroid to mild or severe hypothyroidism. The purpose of the present study was to identify and characterize new variants in the TG gene. We report an Argentine patient with congenital hypothyroidism, enlarged thyroid gland and low levels of serum TG. Sequencing of DNA, expression of chimeric minigenes as well as bioinformatics analysis were performed. DNA sequencing identified the presence of compound heterozygous mutations in the TG gene: the maternal mutation consists of a c.3001+5G > A, whereas the paternal mutation consists of p.Arg296*. Minigen analysis of the variant c.3001+5A performed in HeLa, CV1 and Hek293T cell lines, showed a total lack of transcript expression. So, in order to validate that the loss of expression was caused by such variation, site-directed mutagenesis was performed on the mutated clone, which previously had a pSPL3 vector change, to give rise to a wild-type clone c.3001+5G, endorsing that the mutation c.3001+5G > A is the cause of the total lack of expression. In conclusion, we demonstrate that the c.3001+5G > A mutation causes a rare genotype, altering the splicing of the pre-mRNA. This work contributes to elucidating the molecular bases of TG defects associated with congenital hypothyroidism and expands our knowledge in relation to the pathologic roles of the position 5 in the donor splice site. Highlights: We report a patient with hypothyroidism by mutations in the thyroglobulin gene. Molecular analysis revealed a compound heterozygous for p.R296*/c.3001+5G > A mutations. Minigen analysis shows a total lack of transcript expression. We demonstrate that the c.3001+5G > A mutation alters the splicing of the pre-mRNA. Our results confirm the genetic heterogeneity of thyroglobulin defects.